Evaluation of the APSIM common bean model using different cultivars and water-management scenarios - Seyedreza Amiri; Nader Zakeri; Tayebeh Yousefi (Technology in Agronomy)
The common bean (Phaseolus vulgaris) is a widely consumed legume worldwide and holds significant value in terms of direct human consumption, surpassing all other legume crops combined. This study aimed to assess the applicability of the APSIM common bean model under different water-management conditions and cultivars in southeastern Iran. A two-year field experiment was conducted at the Agricultural Research Station of Shahid Bahonar University of Kerman, Iran, spanning from 2020 to 2021. The experiment followed a split-plot design with a randomized complete block structure and included four replications. The primary irrigation factor consisted of three levels, representing 80%, 60%, and 40% of crop capacity, while the secondary factor encompassed early and late-maturity cultivars. To evaluate the model's performance, simulated and measured grain yield, total dry matter, leaf area index (LAI), and soil water content were compared using the adjusted coefficient of correlation, normalized root mean square errors (nRMSE), and model efficiency (EF). The results indicated a satisfactory agreement between predicted and observed grain yield (nRMSE = 12% and EF = 0.92). Similarly, the agreement between simulated and observed total dry matter was reasonable (nRMSE = 13% and EF = 0.83). The observed and predicted soil water content also exhibited good agreement. Consequently, the APSIM common bean model proves suitable for research purposes, particularly in the areas of irrigation and cultivar selection.